THE EVOLUTION OF SECULARISM IN INDIA AND CHALLENGES: A CRITICAL STUDY - Naidu, S. T.; Unnithan, Arun V (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The concept of secularism has always been a subject of significant debate and discussion in the Indian context. With its diverse cultural, religious, and social fabric, India faces challenges in maintaining a balanced, secular state. The notion of secularism, in the Indian context, is fundamentally different from the Western interpretation. In India, secularism doesn’t imply a strict separation between religion and state; rather, it is an active principle that seeks to promote equality and fairness among all faiths, without privileging any particular belief system. The Constitution of India enshrines secularism as one of its core principles, ensuring that the state treats all religions impartially and guarantees religious freedom. However, the implementation and preservation of secularism in India have been a complex and often contentious issue.